Evolution of mobile-source-related PM2.5 and its associated impacts: Insights from emerging contributors - Junchao Zhao; Zeyu Yang; Huan Liu; Haitong Zhe Sun; Zhenyu Luo; Zhaofeng Lv; Xiaotong Wang; Lijuan Qi; Hang Yin; Yan Ding; Kebin He (Transportation Research Part D: Transport and Environment, 2026)

Experimental investigation on biocementation materials in earthen heritage reinforcement - Jinquan Shi; Lei Zhang; Kebin Ren; Hao Cui; Yang Yang; Yuanjian Liu; Lin Ye; Jianwei Zhang (Geomechanics for Energy and the Environment, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Historical air pollutant emissions and future sustainable pathways of global cement plants - Xizhe Yan; Dan Tong; Zhi Cao; Cuihong Chen; Yaqin Guo; Ruochong Xu; Xinying Qin; Yujia Fu; Yang Liu; Dongsheng Zheng; Kebin He; Qiang Zhang (Resources, Conservation and Recycling, 2024)

Amorphization-sparked superb activity and excellent coke-resistance of Ni nanocatalyst - Zengjian Cai; Yi Cai; Zhe Wang; Shoujie Liu; Xinhu Liang; Hao Ren; Yanan Cao; Zikang Su; Fengyi Shen; Shitu Yang; Guodong Sun; Xiaoxin Yang; et al. (Chemical Engineering Journal, 2024)

The Role of Histone H2B Acetylation Modification in Aluminum-Induced Cognitive Dysfunction - Jie Gao; Wei Liu; Jing Pei; Jing Li; Niping Hao; Shuo Yang; Xiaoming Yang; Danfeng Zou; Kebin Xu; Lifeng Zhang (Biological Trace Element Research, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Changes in Mental Health and EEG Biomarkers of Undergraduates Under Different Patterns of Mindfulness - Miaoling Luo; Quan Gan; Ziyang Huang; Yunxiong Jiang; Kebin Li; Minxiang Wu; Dongxiao Yang; Heng Shao; Yanmei Chen; Yu Fu; Zhuangfei Chen (Brain Topography, 2024)
The effects of short-term mindfulness are associated with the different patterns (autonomic, audio guided, or experienced and certified mindfulness instructor guided mindfulness). However, robust evidence for reported the impacts of different patterns of mindfulness on mental health and EEG biomarkers of undergraduates is currently lacking. Therefore, we aimed to test the hypotheses that mindfulness training for undergraduates would improve mental health, and increase alpha power over frontal region and theta power over midline region at the single electrode level. We also describe the distinction among frequency bands patterns in different sites of frontal and midline regions. 70 participants were enrolled and assigned to either 5-day mindfulness or a waiting list group. Subjective questionnaires measured mental health and other psychological indicators, and brain activity was recorded during various EEG tasks before and after the intervention. The 5-day mindfulness training improved trait mindfulness, especially observing (p = 0.001, d = 0.96) and nonreactivity (p = 0.03, d = 0.56), sleep quality (p = 0.001, d = 0.91), and social support (p = 0.001, d = 0.95) while not in affect. Meanwhile, the expected increase in the alpha power of frontal sites (p < 0.017, d > 0.84) at the single electrode level was confirmed by the current data rather than the theta. Interestingly, the alteration of low-beta power over the single electrode of the midline (p < 0.05, d > 0.71) was difference between groups. Short-term mindfulness improves practitioners’ mental health, and the potentially electrophysiological biomarkers of mindfulness on neuron oscillations were alpha activity over frontal sites and low-beta activity over midline sites.

Long-term spatiotemporal variations in surface NO2 for Beijing reconstructed from surface data and satellite retrievals - Zixiang Zhao; Yichen Lu; Yu Zhan; Yuan Cheng; Fumo Yang; Jeffrey R. Brook; Kebin He (Science of The Total Environment, 2023)

Covalent organic framework-based immunosensor to detect plasma Latexin reveals novel biomarker for coronary artery diseases - Xiuzhen Li; Huaibin Wan; Yang Tian; Jingzhu Wang; Shaohua Xu; Kebin Huang; Hong Liang; Ming Chen (Analytica Chimica Acta, 2023)

Trade-driven changes in China's air pollutant emissions during 2012–2017 - Wenjie He; Hongyan Zhao; Jing Cheng; Yang Liu; Kebin He; Qiang Zhang (Science of The Total Environment, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

The rhizospheric transformation and bioavailability of mercury in pepper plants are influenced by selected Chinese soil types - Sajjad Hussain; Yang Jianjun; Jamshad Hussain; Peiman Zandi; Subhanullah; Xia Xing; Zhang Liandong; Tian Yu; Amjad Ali; Zhang Kebin (Environmental Geochemistry and Health, 2023)

Genome-wide analysis of laccase genes in moso bamboo highlights PeLAC10 involved in lignin biosynthesis and in response to abiotic stresses - Lichao Li; Kebin Yang; Sining Wang; Yongfeng Lou; Chenglei Zhu; Zhimin Gao (Plant Cell Reports, 2020)

Impact of China’s Air Pollution Prevention and Control Action Plan on PM2.5 chemical composition over eastern China - Guannan Geng; Qingyang Xiao; Yixuan Zheng; Dan Tong; Yuxuan Zhang; Xiaoye Zhang; Qiang Zhang; Kebin He; Yang Liu (Science China Earth Sciences, 2019)

Genome-wide identification and expression analysis of brassinosteroid action-related genes during the shoot growth of moso bamboo - Sining Wang; Huayu Sun; Xiurong Xu; Kebin Yang; Hansheng Zhao; Ying Li; Xueping Li; Zimin Gao (Molecular Biology Reports, 2019)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Characteristics of atmospheric non-methane hydrocarbons during haze episode in Beijing, China - Songjun Guo; Jihua Tan; Jingchun Duan; Yongliang Ma; Fumo Yang; Kebin He; Jimin Hao (Environmental Monitoring and Assessment, 2012)

Characteristics of atmospheric non-methane hydrocarbons in Foshan City, China - Jihua Tan; Songjun Guo; Yongliang Ma; Kebin He; Fumo Yang; Yongchang Yu; Jiewen Wang (Environmental Monitoring and Assessment, 2011)

Temporal variability in fine carbonaceous aerosol over two years in two megacities: Beijing and Toronto - Fumo Yang; Jeffrey Brook; Kebin He; Fengkui Duan; Yongliang Ma (Advances in Atmospheric Sciences, 2010)